Health Care Professionals: A Synthesis and Integration of Select Concepts and Theories in the Study of Mental Illness through the Society, Culture, Personality (SCP) Model - Fredericks, Janet (2013)
Abstract: The purpose of this article is to present select concepts and theories in the study of mental illness pertinent for health care professionals. The society-culture-personality (SCP) model is examined in relationship to mental illness so that health care professionals are well-informed on the severity of these disorders in order to provide quality care regardless of geographic location. The society-culture-personality (SCP) model is examined in relationship to some of the most severe forms of mental illness, namely, schizophrenia and major depressive disorder. Social meaningful interaction (SMI) is examined in the development of personality and how social and cultural norms affect the development of the individual. Psychoses are major mental disorders in the United States and in other parts of the world. It is important for health care providers to be knowledgeable about mental illness and the role social class, culture and family play in defining mental illness. By having a thorough understanding of the select concepts and theories involved in the study of mental illness we are hoping that the ingredients of quality, affordability, availability, accessibility, and continuity of care are extended to all members of society